"The Greatest Living Critic": Christiana Herringham and the Practice of Connoisseurship. (3rd April 2017) - Clarke, Meaghan
Abstract : Christiana Herringham (1851–1929) was a founder and benefactor of the National Art Collections Fund in 1903. Her career as an artist and art writer is less well known. Herringham undertook early experimentation with tempera painting alongside her translation of Cennino Cennini's (c.1370–c.1440) treatise on painting techniques. Herringham's meticulous approach to understanding "medieval art methods" was a catalyst for the foundation of the Society of Painters in Tempera. Her writing for the art press, most notably for the Burlington Magazine where she was on the Consultative Committee, reveals her expertise on the technical aspects of connoisseurship. This article traces the development of Herringham's "scientific" method and highlights her pivotal role in a series of interconnecting networks. Knowledge and understanding of techniques and materials gave her a particular authority, just at the point that art history as a discipline was developing. Herringham's interventions point to the need for a re-evaluation of male-centered narratives about the formation of art history.